2022
DOI: 10.1093/aobpla/plac021
|View full text |Cite
|
Sign up to set email alerts
|

Fungal association and root morphology shift stepwise during ontogenesis of orchidCremastra appendiculatatowards autotrophic nutrition

Abstract: Background and Aims The chlorophyllous, terrestrial orchid Cremastra appendiculata from East Asia is unique concerning its fungal mycorrhiza partners. The initially mycoheterotrophic protocorms exploit rather specialised non-rhizoctonia saprotrophic Psathyrellaceae. Adult individuals of this orchid species are either linked to Psathyrellaceae being partially mycoheterotrophic or form mycorrhiza with fungi of the ubiquitous saprotrophic rhizoctonia group. This study provides new insights on nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…3d), a fully mycoheterotrophic species, and its photosynthetic sister species, Cremastra appendiculata (Fig. 3c), within the C. appendiculata species complex (Yagame et al 2021, Zahn et al 2022. It has been observed that C. aphylla, which inhabits dark…”
Section: Local Adaptation and The Evolution Of Reproductive Isolationmentioning
confidence: 98%
See 1 more Smart Citation
“…3d), a fully mycoheterotrophic species, and its photosynthetic sister species, Cremastra appendiculata (Fig. 3c), within the C. appendiculata species complex (Yagame et al 2021, Zahn et al 2022. It has been observed that C. aphylla, which inhabits dark…”
Section: Local Adaptation and The Evolution Of Reproductive Isolationmentioning
confidence: 98%
“…3d), a fully mycoheterotrophic species, and its photosynthetic sister species, Cremastra appendiculata (Fig. 3c), within the C. appendiculata species complex (Yagame et al 2021, Suetsugu et al 2022, Zahn et al 2022). It has been observed that C. aphylla , which inhabits dark shaded understory, is consistently associated with wood‐decaying Psathyrellaceae, whereas C. appendiculata , which inhabits somewhat more open habitats, is mainly associated with rhizoctonias.…”
Section: Local Adaptation and The Evolution Of Reproductive Isolationmentioning
confidence: 99%